Patterns of changing cancer risks with time since diagnosis of a sibling. Issue 8 (10th October 2014) - Lee, Myeongjee; Czene, Kamila; Rebora, Paola; Reilly, Marie
<x xml:space="preserve">Abstract</x> Family history is a well‐known risk factor for many cancers. However, it is important to know if/how the familial risk of cancer changes over time. For each of four major cancers (colorectal, breast, prostate and melanoma), we identified siblings of cancer patients (case siblings) and siblings of matched cancer‐free controls sampled from Swedish population‐based registers. Effects of age and time since diagnosis on sibling risks were examined using Poisson regression and presented graphically as smoothed hazard ratios (HRs). Screening effects were investigated by comparing hazards before/after the introduction of mammography for breast cancer and prostate‐specific antigen (PSA) testing for prostate cancer. Case siblings had higher cancer incidence than control siblings for all cancers at all ages, with overall incidence rate ratios (IRRs) of 2.41 (95% confidence interval 2.14–2.71) for colorectal cancer, 2.37 (2.24–2.52) for breast cancer, 3.69 (3.46–3.93) for prostate cancer and 3.20 (2.72–3.76) for melanoma. Risks were highest in siblings who were young when the first cancer was diagnosed in the family, with siblings aged 30–40 having IRR 9.05 (3.03–27.00) for colorectal cancer and 4.30 (2.87–6.45) for breast cancer. Smoothed HRs remained fairly constant for up to 20 years except for prostate cancer, where the HR decreased steeply during the first few years. After introduction of PSA testing, men had higher incidence of prostate cancer shortly after diagnosis in a brother, but no such screening effect was found for breast cancer. Our findings can help inform the screening and counseling of family members of cancer patients.